2020
DOI: 10.3168/jds.2019-18036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fecal fermentation profile and bacterial community in organically fed dairy cows consuming forage-rich diets with different particle sizes

Abstract: Organic cattle farming encourages the use of foragerich diets, and the reduction of particle size has been suggested as an approach to improve forage utilization and enhance nutrient intake of cows. However, reducing forage particle size increases passage rate, as well as the flow of potentially fermentable nutrients out of the rumen, and the consequences for hindgut fermentation have not been evaluated yet. This study evaluated the effects of decreasing dietary forage particle size on the fecal short-chain fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
(78 reference statements)
2
10
0
Order By: Relevance
“…At the genus level, similar to the study of Castillo-Lopez et al ( 49 ), we found that Ruminococcaceae_UCG-005, Ruminococcaceae_UCG-010 , and Rikenellaceae_RC9_gut_group were the most abundant genera in the fecal bacteria community of dairy cows. The relative abundance of the family Ruminococcaceae , such as the genus Ruminococcaceae_UCG-005, Ruminococcaceae_UCG-010, Ruminococcaceae_UCG-013 , and Ruminococcaceae_UCG-014 , were all higher in the calcium propionate treatment groups than the CON group.…”
Section: Discussionsupporting
confidence: 90%
“…At the genus level, similar to the study of Castillo-Lopez et al ( 49 ), we found that Ruminococcaceae_UCG-005, Ruminococcaceae_UCG-010 , and Rikenellaceae_RC9_gut_group were the most abundant genera in the fecal bacteria community of dairy cows. The relative abundance of the family Ruminococcaceae , such as the genus Ruminococcaceae_UCG-005, Ruminococcaceae_UCG-010, Ruminococcaceae_UCG-013 , and Ruminococcaceae_UCG-014 , were all higher in the calcium propionate treatment groups than the CON group.…”
Section: Discussionsupporting
confidence: 90%
“…On the family level, Prevotellaceae and Succinivibrionaceae linearly increased with increasing BP level, which was also observed in several genera belonging to these families, such as Prevotellaceae UCG-001, Prevotella 1, as well as Ruminobacter, which might be due to their ability to grow under low pH conditions (Castillo-Lopez et al, 2020). Indeed, the abundance of Prevotellaceae UCG-001 was negatively correlated with the fecal pH.…”
Section: Microbial Communitymentioning
confidence: 76%
“…During the whole first week of life, fecal butyrate concentration was higher than propionate, suggesting an increased butyrogenesis in the gut of young calves during the first week, likely to stimulate the intestinal growth and maturation (Górka et al, 2011;Steele et al, 2016). Starting from d 7, both ruminal and fecal fermentation profile resembled that of adult cattle fecal fermentation (Castillo-Lopez et al, 2020, 2021b.…”
Section: Discussionmentioning
confidence: 93%